Relationship between personality traits and sense of urgency: A study of Repso Malaysia - Ahmad, Hartini; Jalil, Johari (IBIMA Publishing, 2013)
Sense of urgency is a crucial element of a successful change process.This research was designed to investigate the relationship between personality traits and sense of urgency. It employed quantitative method in examining the said relationship against a real-life scenario of major change in a single entity of a Multi National Corporation – Repso Malaysia.Through on-line questionnaire, a total of 247 employees of various functions, job levels and cross border cultures made up the case study of this research. The findings of the research confirmed the positive relationship of conscientiousness, extra version, agreeableness and openness to experiences with sense of urgency.The trait of neurotic ism revealed a negative but non-significant relationship to sense of urgency and duly supported with justification by the research. The paper addresses the limitations; first, the use of modified instrument lacks the established knowledge of its validity and reliability within the contexts of the case organization.Secondly, the researcher has no control on who actually responds to the questions.Thirdly, the research sample represents only single entity and cannot be generalized to the total population.Other than contributing to the body of knowledge over a subject which is empirically scarce, the research further renewed the importance of micro level analysis of an organization i.e. individuals rather than only the macro level.